The Effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on Return on Equity (RoE) at PT Aneka Tambang, Tbk, Years 2010 - 2017 - Jati, Waluyo; Andini, Tiya Sri (Universitas Negeri Makassar, 2019)
The company wants an optimal profit for the business being run. This study aims to determine the effect of the current ratio (CR) on return on equity (ROE), the effect of debt to equity ratio (DER) on return on equity (ROE), and to determine the effect of current ratio (CR) and debt to equity ratio (DER) simultaneously on return on equity (ROE) at PT Aneka Tambang, Tbk in the period 2010 - 2017. The research method used is descriptive quantitative. The data used are secondary data in the form of PT Aneka Tambang, Tbk's financial statements for the period 2010-2017. The analytical method used is the classic assumption test, multiple linear regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing with t-test and F test using SPSS version 20.0. The results showed no significant effect of the current ratio (CR) on return on equity (ROE), there was no significant effect of debt to equity ratio (DER) on return on equity (ROE), and there was no significant effect between the current ratio (CR) and debt to equity ratio (DER) together against return on equity (ROE). Current ratio (CR) and debt to equity ratio (DER) have a very strong relationship to return on equity (ROE). The contribution rate of the variable current ratio (CR) and the debt to equity ratio (DER) to return on equity (ROE) is 61.9%.